Maximizing Nutrition and Cost-Effectiveness: Sustainable Strategies for School Feeding and Gardening for Greater Impact in Cambodian Schoolchildren - Phuong Vichea, Vanna; Sockcheng, Sim; Sombath, KEO (WorldFish, 2024)
This policy brief evaluates the cost-effectiveness, nutritional adequacy, and sustainability of Cambodia's three School Feeding Program (SFP) modalities: state-run, WFP-run, and school-gardening programs. Data from the 2022-2023 school year revealed disparities in implementation. The state-run model was the most cost-efficient, spending USD 38.9 per child annually compared to USD 55.24 in WFP-managed schools. School-gardening programs, at USD 53.08 per child, offered added benefits like environmental education, community engagement, and income generation but faced higher startup and operational costs. This brief emphasizes a holistic approach to school feeding, combining cost-effective practices with nutritional adequacy and sustainability. Addressing challenges and leveraging opportunities can significantly enhance Cambodia’s SFP impact on child nutrition, health, and education.